(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
According to many constitutions, majority rule respect for minorities’ rights are emphasized.In today’s world, democracy mostly refers to a form of government in which the people themselves are incharge. The mission of the National Commission for Minority Affairs (NCMA). It is not defined in theConstitution of India, but minorities based on religion, language, and culture are recognized protectedby the Indian government. India’s government established the National Council for Minorities to addressthe concerns of Muslims, Christians, Sikhs, Buddhists, Parsis. Minority rights protections in Indiahave evolved over time, but it wasn’t until the British ruled the country that they began to receive newattention or configuration.